Natural Resources and Control Processes - Wang, Lawrence K.; Wang, Mu-Hao Sung.; Hung, Yung-Tse.; Shammas, Nazih K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This edited book has been designed to serve as a natural resources engineering reference book as well as a supplemental textbook. This volume is part of the Handbook of Environmental Engineering series, an incredible collection of methodologies that study the effects of pollution and waste in their three basic forms: gas, solid, and liquid. It complements two other books in the series including Environmental and Natural Resources Engineering and Integrated Natural Resources Management that serve as a basis for advanced study or specialized investigation of the theory and analysis of various natural resources systems. This book covers the management of many waste sources including those from agricultural livestock, deep-wells, industries manufacturing dyes, and municipal solid waste incinerators. The purpose of this book is to thoroughly prepare the reader for understanding the sources, treatment and control methods of toxic wastes shown to have harmful effectson the environment. Chapters provide information on some of the most innovative and ground-breaking advances in waste characterization, control, treatment and management from a panel of esteemed experts.
Management of Livestock Wastes for Water -- Resources Protection -- Application of Natural Processes for Environmental Protection -- Proper Deep-Well Waste Disposal for Water Resources Protection -- Treatment and Management of Industrial Dye Wastewater for Water Resources Protection -- Health Effects and Control of Toxic Lead in the Environment -- Municipal and Industrial Wastewater Treatment Using Plastic Trickling Filters for BOD And Nutrient Removal -- Chloride Removal for Recycling Fly Ash from Municipal Solid Waste Incinerator -- Recent Evaluation of Early Radioactive Disposal and Management Practice -- Recent Trends in the Evaluation of Cementitious Material in Radioactive Waste Disposal -- Extensive Monitoring System of Sediment Transport for Reservoir Sediment Management -- Glossary of Land and Energy Resources Engineering.
Keywords: Refuse and refuse disposal; Environmental engineering; Biotechnology; Bioremediation; Water; Hydrology; Environment; Pollution; Environmental chemistry; Waste Management/Waste Technology; Environmental Engineering/Biotechnology.; Water; Environmental Sciences; Pollution; Environmental Chemistry